2005
DOI: 10.1128/jvi.79.1.602-608.2005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Productive Human Immunodeficiency Virus Infection of CD1a-Sorted Myeloid Dendritic Cells

Abstract: Myeloid, CD1a-sorted dendritic cells (MDC) productively replicated human immunodeficiency virus strains encoding envelope genes of either primary X4R5 or R5 strains for up to 45 days. Cell-free supernatant collected from long-term infected MDC, which had been exposed to an X4R5 virus 45 days earlier, was still infectious when placed over activated T cells. These data imply that DC can act as a persistent reservoir of infectious virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…While previous studies have investigated HIV infection of LCs, the ability of uninfected LCs to mediate transinfection of target cells remains unknown (2,22,23,30). We observed that activated LCs incubated with HIV were able to stimulate transinfection of target cells, while unactivated LCs were not.…”
mentioning
confidence: 71%
“…While previous studies have investigated HIV infection of LCs, the ability of uninfected LCs to mediate transinfection of target cells remains unknown (2,22,23,30). We observed that activated LCs incubated with HIV were able to stimulate transinfection of target cells, while unactivated LCs were not.…”
mentioning
confidence: 71%
“…Highly active antiretroviral therapy significantly suppresses the HIV viral load but is unable to eradicate the virus from the body, leaving the possibility of the persistence of viral reservoirs. HIV-infected DCs act as viral reservoirs for long-term HIV transmission in vivo [22,23,24]. Identifying ways to trigger innate and adaptive immune responses to inhibit DC-endorsed HIV replication represents a potential strategy to limit HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, HIV-1 can preferentially infect and replicate in DCs (cis-infection pathway) by exploiting innate immune signaling through TLR8 and DC-SIGN [18,19,20,21]. Increasing evidence indicates that HIV-infected DCs act as viral reservoirs for long-term HIV transmission in vivo [22,23,24]. Although DCs are susceptible to both R5 and X4 HIV-1 strains, HIV-1 replication is generally less productive in DCs than in CD4 + T cells, presumably because of the expression of restriction factors in DCs that block HIV-1 replication.…”
Section: Introductionmentioning
confidence: 99%
“…As negative control, 293T cells infected with wt VV were transfected with plasmid pSC59. When GFP-positive cells appeared, cells were sorted by flow cytometry as described (Popov et al, 2005).…”
Section: Generation Of Recombinant Vvsmentioning
confidence: 99%